PHYTOCHEMICAL SCREENING AND ANALYSIS POLYPHENOLIC ANTIOXIDANT ACTIVITY OF METHANOLIC EXTRACT OF WHITE DRAGON FRUIT (Hylocereus undatus) - VH, Elfi Susanti; Utomo, Suryadi Budi; Syukri, Yandi; Redjeki, Tri (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2012)
White dragon fruit is a well known and widely used herbal medicine, especially in Asia, which contains several interesting bioactive constituents and possesses health promoting properties. The aim of this study was to analyze for the bioactive compounds, evaluate total phenolic contents and antioxidant capacities of methanolic extract of white dragon fruit. The antioxidant activity was determined by the 1,1-diphenyl-2-picrylhydrazyl (DPPH) free radical scavenging activity assay. Total phenolic content were determined by Folin-Ciocalteu method. Phytochemical screening of the white dragon fruit showed the presence of triterpenoid, alkaloid, flavonoid and saponin. The extract exhibited strong antioxidant activity with IC50 of 193 μg/mL, and total phenolic content of 246 μg/mL in 1 Kg dry extract.Key words: antioxidant activity, total phenolic, DPPH, white dragon fruit